Water quality of aquatic ecosystems of Akmola region - Zhartybaeva, M.G.; Tulegenova, S.E.; Muntaev, N. (Fundamental and Experimental Biology, 2022)
Currently, the issue of protecting natural resources from polluting and preventing pollution requires worldwide attention. In general, water resources are becoming an invaluable resource that explains the sustainable development of any state. Rational use and protection of water sources is becoming one of the most pressing issues in our country. Pollution of water sources, in turn, affects the deterioration of water quality, living organisms that live in water sources (algae, fish, etc.), and the health of consumers. Since water is the most important resource in the world, it is a task to protect and prevent environ mental risk. Therefore, to monitor the aquatic ecosystems of Akmola region, the research team conducted research in laboratory conditions, taking water samples from water bodies (Nura, Ishim Riversand Taldykol, Maybalyk, and Zhaltyrkol Lakes) from a practical trip organized by the research group. Research studies on water samples taken from water bodies showed that the water was polluted, and in some indicators the maximum rural concentration was exceeded. It is clear that pollutants affect water biota, although in most cases they are not the cause. According to water samples, the level of pollution of water sources was assessed. Protection of Water Resources in general from pollutants is one of the strategic tasks of the country.